Cardboard Bed Without Mattress Is Ineffective in Improving the body Contact Pressure-a Preliminary Study Using a Dummy Model. (8th December 2021) - Hamanishi, Seiji
Objective: This study aimed to describe and evaluate the dispersion of body-mattress contact pressure on a cardboard bed and investigate whether the cardboard bed has a positive effect on evacuees' musculoskeletal burden. Materials and Methods: A high-performance nursing simulator was used to measure the contact pressure and the body surface contour area of the bed, and these values were collected with the patient in the supine position using the Body Pressure Measurement System. Data of each test were acquired 10 times and were compared among 4 conditions (plastic sheet, cardboard bed, cardboard bed with a blanket, and cardboard bed with a mattress-topper). The data analysis for body-mattress contacts pressure and the surface contour area of the whole body, head, chest, and buttocks were conducted by one-way repeated analysis of variance and Bonferroni post-hoc test. Results: The average body-contact pressure on the cardboard bed did not decrease compared with that on the floor with plastic sheets. In contrast, the body surface contour area was significantly different among any other conditions, but the gap was only approximately 16%. However, the body-contact pressure and the body surface contour area were improved when a mattress-topper was added on the cardboard bed. When a blanket was laid on the cardboard bed, the contact area was increased. Conclusion: Our results indicate that the pressure dispersion ability of the cardboard bed was not sufficient; however, adding the mattress-topper or the blanket could contribute to an improvement in the evacuees' musculoskeletal burden. Many evacuees lay a mattress topper or futon on a cardboard bed after installing cardboard beds. Our findings may also support the scientific validity of the evacuees' actual sleeping style in Japan. This preliminary study provides the basis for future research on exploring an appropriate sleeping bed condition in evacuee shelters.